2019
DOI: 10.1530/jme-19-0034
|View full text |Cite
|
Sign up to set email alerts
|

BAG1L: a promising therapeutic target for androgen receptor-dependent prostate cancer

Abstract: Androgens are important determinants of normal and malignant prostate growth. They function by binding to the C-terminal ligand-binding domain (LBD) of the androgen receptor (AR). All clinically approved AR-targeting antiandrogens for prostate cancer therapy function by competing with endogenous androgens. Despite initial robust responses to androgen deprivation therapy, nearly all patients with advanced prostate cancer relapse with lethal castration-resistant prostate cancer (CRPC). Progression to CRPC is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…We have previously reported that BAG1L uses its conserved BAG domain to interact with the AR N-terminal domain (NTD) to enhance its activity ( Cato et al., 2017 ; Shatkina et al., 2003 ). Because the AR NTD is an important domain for the transactivation function of the AR ( Yu et al., 2020 ) and the AR a key driver of prostate cancer, small molecules targeting the BAG-AR NTD interaction interface would inhibit AR activity and function as prostate cancer therapeutics ( Lee et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that BAG1L uses its conserved BAG domain to interact with the AR N-terminal domain (NTD) to enhance its activity ( Cato et al., 2017 ; Shatkina et al., 2003 ). Because the AR NTD is an important domain for the transactivation function of the AR ( Yu et al., 2020 ) and the AR a key driver of prostate cancer, small molecules targeting the BAG-AR NTD interaction interface would inhibit AR activity and function as prostate cancer therapeutics ( Lee et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) has been the mainstay of management for advanced PCa. Despite the initial strong responses to androgen deprivation therapy, the majority of patients with advanced PCa relapse with fatal castration-resistant PCa (CRPC) [ 60 ]. According to our data, IRX4 and its isoforms are differentially expressed depending on the cell lines’ androgen responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The AR-BF3 targeting compounds containing a benzimidazole or benzindole scaffold were collected from Cherkasov et al's publications 28,30 and were further classified into five categories according to their substitution groups (Table S1). Representative compounds of each series (15,21,24,32,38,43,47,52,54, and 12m) were selected for the following computational studies. Among these compounds, the ternary crystal structure of 32 bound AR complexed with an endogenous agonist testosterone (TES) (AR/TES/32) (PDB ID: 4HLW) was used as the template to model the binding poses of the other chosen derivatives (15, 21, 24, 38, 43, 47, 52, 54, and 12m) in the BF3 site of AR/TES.…”
Section: Methodsmentioning
confidence: 99%